Analysis of the volume of competitive loads of leading foreign riders in modern cycling-highway - Kubeev, A. V.; Oganesyan, A. A.; Savenkova, E. A.; Matina, V. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the parameters of the volume of competitive load among the leading foreign racers in different age periods.